1991
DOI: 10.1111/j.1600-0668.1991.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Human Reactions to Emissions from Building Materials in Climate Chambers. Part I: Clinical Data, Performance and Comfort

Abstract: The purpose of this study was to evaluate whether asthmatic reactions and changes in tear film quality could be prmohd by exposing subjects to missions from building materiuls in climate chambers. Twenty asthmatics and 5 healthy controls were exposed to (I) gypsum board hung with waterbonze painted wallpaper; (2) rubber floor covering; (3) n y h carpet with rubber mat; (4) particle board coated with acid-curing paint; and (5) m test materials in climate chambers for 6 h. Participants recorded symptoms by fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
3
14
0
1
Order By: Relevance
“…In the studies of Sundell et al (1994), copying machines were observed to pose a significant risk for SBS symptoms. In addition, studies in climate chambers have demonstrated that emissions from office equipment (Wolkoff et al, 1992) and building materials such as vinyl and textile floor covering (Johnsen et al, 1991) can induce symptoms in humans typical of those reported in problem buildings. Sick building symptoms have also been associated with VOC levels in Swedish office buildings ).…”
Section: Multifactorial Genesis Of Sick Building Symptomsmentioning
confidence: 99%
“…In the studies of Sundell et al (1994), copying machines were observed to pose a significant risk for SBS symptoms. In addition, studies in climate chambers have demonstrated that emissions from office equipment (Wolkoff et al, 1992) and building materials such as vinyl and textile floor covering (Johnsen et al, 1991) can induce symptoms in humans typical of those reported in problem buildings. Sick building symptoms have also been associated with VOC levels in Swedish office buildings ).…”
Section: Multifactorial Genesis Of Sick Building Symptomsmentioning
confidence: 99%
“…The tear film is less stable among office workers with eye symptoms (Franck, 1986; Kjærgaard et al., 1993) and decreased tear film stability is related to indoor air pollutant exposures (Johnsen et al., 1991; Kjærgaard et al., 1989, 1999; Mølhave et al., 2002; Pan et al., 2000). Similarly, damaged conjunctival epithelium has been related to symptoms (Franck, 1986) and in two studies to indoor exposures (Mølhave et al., 1995; Wolkoff et al., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The TVOC concept, using the TVOC concentration of 3 mg/m3 as an indicator, may in this case overestimate the impact of the paint on indoor air quality due to the low biological effect of propanediol. In general, waterborne paints are recognized as having a modest impact on the indoor air quality Johnsen et al, 1991).…”
Section: Discussionmentioning
confidence: 99%